LATAR BELAKANG BERDIRINYA JAM'IYAH MAHMUDIYAH LI THALIBIL KHAIRIYAH TANJUNG PURA LANGKAT: - ., Zainal Dahlan (Program Studi Pendidikan Agama Islam, 2017)
This study aims to provide a complete and precise picture associated with the religious, social, political, and intellectual conditions that melatarlakangi establishment of Jam'iyah Mahmudiyah Li Thalibil Khairiyah Tanjung Pura Langkat. The findings of the research inform that: first, Jam'iyah Mahmudiyah Li Thalibil Khairiyah Tanjung Pura Langkat was born on 22 Muharram 1330/31 December 1912 in East Sumatra on the initiative of Sultan Langkat along with ulama and society. Secondly, there are several factors behind the establishment of Jam'iyah Mahmudiyah Li Thalibil Khairiyah, namely: religious factors, Jam'iyah Mahmudiyah was established with the aim to socialize ideology in accordance with Islamic teachings and in accordance with those adopted by Sultan Langkat. Social factors, Jam'iyah Mahmudiyah was established with the aim to legitimize the position of Sultan Langkat. Political factors, for the Sultan to get support from the community and in fact the institution is used very well by Sultan Langkat in his political navigation. The intellectual factor, for the society prosperous through the education provided by Sultan Langkat.